Exploration of the Keteng-Keteng Musical Instrument in Learning the Surface Area of Cylinders at SMPS Deli Murni Bandar Baru - Sihombing, Artha Hadia; Tambunan, Hardi; Simanjuntak, Ruth M (Lembaga Penelitian dan Pendidikan Mandala, 2025)
This research aims to explore the potential of traditional musical instruments.Keteng-Ketengas a contextual media in learning the concept of surface area of cylinders at the junior high school level. This musical instrument is known in the Batak Karo culture and has a distinctive cylindrical shape, making it relevant for use in understanding spatial figures. The research was conducted at SMPS Deli Murni Bandar Baru with an ethnomathematics approach. The method used was descriptive qualitative with observation, interview, and documentation techniques. The results showed that the use of Keteng-Keteng in learning was able to improve students' understanding of the surface area of cylinders and create a contextual, meaningful learning atmosphere rooted in local culture.